Sorotan dan Kritikan Awal Terhadap Deklarasi Ke Arah Suatu Etika Global (Declaration Towards a Global Ethic) - Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
Declaration Towards a Global Ethic is a proclamation that is declared in Parliament of the World’s Religions in 1993 in Chicago, USA. The consensus reached between the representatives of religions on this declaration is a new and important achievements in inter-religious dialogue. Therefore, this paper will discuss some important aspects that underlie the preparation of the declaration in particular regarding the process of drafting the declaration, some defined criteria, and also content and methods used in this declaration. This paper also identifies several issues in the declaration that raises some questions of its position as a universal declaration for every religion and humankind. In conclusion, this declaration can not be certified as a universal declaration as long as some of the questions raised are not addressed and resolved in advance.